Self-assembled hyaluronic acid nanoparticles for the topical treatment of inflammatory skin diseases: Beyond drug carriers - Lee, Wang Hee; Kim, Wook (Journal of Controlled Release, 2024)
Inflammatory skin diseases represent a significant health concern, affecting approximately 20–25% of the global population. These conditions not only reduce an individual's quality of life but also impose a huge burden on both humanity and society. However, addressing these challenges is hindered by their chronic nature, insufficient therapeutic effectiveness, and the propensity for recurrence and adverse side effects. Hyaluronic acid (HA) has emerged as a potential solution to these barriers, owing to its excellent attributes such as biocompatibility, non-toxicity, and targeted drug delivery. However, its practical application has been limited because endogenous hyaluronidase (HYAL) rapidly degrades HA in inflamed skin thus reducing its ability to penetrate deep into the skin. Interestingly, recent research has expanded the role of self-assembled HA-nanoparticles (HA-NPs) beyond drug carriers; they are resistant to HYAL, thereby enabling deep skin penetration, and possess inherent anti-inflammatory properties. Moreover, these abilities can be fine-tuned depending on the conditions during particle synthesis. Additionally, their role as a drug delivery system holds potential for use as a multi-target drug or hybrid drug. In conclusion, this review aims to specifically introduce and highlight the emerging potential of HA-NPs as a topical treatment for inflammatory skin conditions.
Keywords: Condition; Drug carrier; Global population; Health concerns; Inflammation; Inflammatory skin disease; Self assembled nanoparticles; Skin disease; Topical therapeutic; Topical treatments; Drug Carriers; Hyaluronic Acid; Nanoparticles; Quality of Life; Skin; Drug carrier; Hyaluronic acid; Inflammation; Inflammatory skin diseases; Self-assembled nanoparticle; Topical therapeutics